Can Bureaucrats Break Trust? Testing Cultural and Institutional Theories of Trust with Chinese Panel Data. (September 2022) - Fairbrother, Malcolm; Mewes, Jan; Wilkes, Rima; Wu, Cary; Giordano, Giuseppe Nicola
What is the relationship between trust and the quality of political institutions in a society? According to an influential cultural perspective, social trust—the belief that most people can be trusted—is a value inculcated during individuals' formative years, and remains fixed afterward. A second perspective holds that social trust reflects experiences throughout the life course, particularly interactions with public institutions and officials. The authors test these cultural and institutional theories using data from three waves of the China Family Panel Studies, assessing how political and social trust respond to treatment by public officials that respondents consider unfair. The authors find that such experiences, which they show in many cases likely meant being a victim of corruption, are associated with declines in trust. Yet the effects are short lived: within two years both types of trust revert to their original levels. These results therefore provide mixed support for both theories and suggest a reconciliation between them.